Playing success and local market size in Spanish Football League: Can small cities dream of winning teams? - Sanchez Santos, J. M.; Dopico, J.; Castellanos, P. (Journal of Quantitative Analysis in Sports, 2012)
This article investigates the influence of local market size on playing success in professional Spanish football. In order to examine this relationship, several regressions were run for linear, beta and fractional logit models, using various proxies of local market size as explanatory variables. The evidence emerging from our analysis suggests that the advantage of big-market teams results in substantial dominance by a very small group of clubs. Nevertheless, this advantage does not actually prevent teams that are located in areas with a small market size from having at least regular opportunities for success. Furthermore, the econometric modelling and the evidence obtained provide a rational basis for supporting the idea of promoting the creation of a cross-national league in Europe (the European Superleague).